Increased Mobilization of Mesenchymal Stem Cells in Patients With Essential Hypertension: The Effect of Left Ventricular Hypertrophy. Issue 12 (20th October 2014) - Marketou, Maria E.; Parthenakis, Fragiskos I.; Kalyva, Athanasia; Pontikoglou, Charalampos; Maragkoudakis, Spyros; Kontaraki, Joanna E.; Zacharis, Evangelos A.; Chlouverakis, Gregory; Patrianakos, Alexandros; Papadaki, Helen A.; Vardas, Panos E.
<x xml:space="preserve">Abstract</x> Stem cells have great clinical significance in many cardiovascular diseases. However, there are limited data regarding the involvement of mesenchymal stem cells (MSCs) in the pathophysiology of arterial hypertension. The aim of this study was to investigate the circulation of MSCs in patients with essential hypertension. The authors included 24 patients with untreated essential hypertension and 19 healthy individuals. Using flow cytometry, MSCs in peripheral blood, as a population of CD45−/CD34−/CD90+ cells and also as a population of CD45−/CD34−/CD105+ cells, were measured. The resulting counts were translated into the percentage of MSCs in the total cells. Hypertensive patients were shown to have increased circulating CD45−/CD34−/CD90+ compared with controls (0.0069%±0.012% compared with 0.00085%±0.0015%, respectively; P=.039). No significant difference in circulating CD45−/CD34−/CD105+ cells was found between hypertensive patients' and normotensive patients' peripheral blood (0.018%±0.013% compared with 0.015%±0.014%, respectively; P=.53). Notably, CD45−/CD34−/CD90+ circulating cells were positively correlated with left ventricular mass index (LVMI) (r=0.516, P<.001). Patients with essential hypertension have increased circulating MSCs compared with normotensive patients, and the number of MSCs is correlated with LVMI. These findings contribute to the understanding of the pathophysiology of hypertension and might suggest a future therapeutic target.